ANALISIS PROSES PENGENDALIAN PERSEDIAAN DEGAN METODE ECONOMIC ORDER QUANTITY DI MDLY GOLD - Resista Vikaliana; Sekartadji Laora (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2023)
MDLY Gold is a small and medium business partner (MSME) engaged in the fashion sector that has been established since 2017. As of 2022, MDLY Gold successfully has 9 production and retail locations throughout the major islands of Indonesia with the main outlet located in Tanah Abang, Jakarta. Center. However, ordering MDLY Gold raw materials requires a lead time of 2 weeks. So this will affect the long production time so that it causes losses for MDLY Gold. Therefore, to maximize raw material inventory and reduce losses, we can analyze using the Economic Order Quantity method. Through solving the inventory control problem, the total Economic Order Quantity (EOQ) of raw material inventory for MDLY Gold production is 27,413.8 Yards during January to June. This EOQ aims to manage inventory that can optimize the total cost consisting of ordering costs and holding costs. Besides this, MDLY Gold must reorder when the stock reaches a reorder point of 17,668.4 Yards with additional supplies needed if there is no shortage of raw materials or safety stock of 10,112.24 Yards. Determination of ROP and SS is useful for MDLY Gold to be able to find out when is the best time to place an order besides there is an order lead time, so that raw materials will arrive on time and the production process will run smoothly without any problems in inventory control.